Mucosal and systemic immune responses after a single intranasal dose of nanoparticle and spore-based subunit vaccines in mice with pre-existing lung mycobacterial immunity - Vergara, Emil Joseph; Tran, Andy Cano; Kim, Mi-Young; Mussá, Tufária; Paul, Matthew J.; Harrison, Thomas; Reljic, Rajko (Frontiers in Immunology, 2023)
Tuberculosis (TB) is a major global health threat that claims more than 1.6 million lives annually. With a quarter of the global population harbouring latent TB, post-exposure vaccination aimed at high-risk populations that could develop active TB disease would be of great public health benefit. Mucosal vaccination is an attractive approach for a predominantly lung disease like TB because it elicits both local and systemic immunity. However, the immunological consequence of mucosal immunisation in the presence of existing lung immunity remains largely unexplored. Using a mycobacterial pre-exposure mouse model, we assessed whether pre-existing mucosal and systemic immune responses can be boosted and/or qualitatively altered by intranasal administration of spore- and nanoparticle-based subunit vaccines. Analysis of lung T cell responses revealed an increasing trend in the frequency of important CD4 and CD8 T cell subsets, and T effector memory cells with a Th1 cytokine (IFNγ and TNFα) signature among immunised mice. Additionally, significantly greater antigen specific Th1, Th17 and IL-10 responses, and antigen-induced T cell proliferation were seen from the spleens of immunised mice. Measurement of antigen-specific IgG and IgA from blood and bronchoalveolar lavage fluid also revealed enhanced systemic and local humoral immune responses among immunised animals. Lastly, peripheral blood mononuclear cells (PBMCs) obtained from the TB-endemic country of Mozambique show that individuals with LTBI showed significantly greater CD4 T cell reactivity to the vaccine candidate as compared to healthy controls. These results support further testing of Spore-FP1 and Nano-FP1 as post-exposure TB vaccines.